CRIZA SERIALELOR ŞI ACCESUL LA RESURSELE INFORMAŢIONALE ŞTIINŢIFICE DIN BIBLIOTECILE REPUBLICII MOLDOVA - ŢURCAN, Nelly (BIBLIOPOLIS, 2020)
The article is about the results of the 2010 librarian year, focused on the examination and implementation of the web 2.0 technologies. The author mentions the essence of the Library 2.0, the changes in the user’s conduit, the new modern information and communication tools.